2016
DOI: 10.5194/angeo-34-609-2016
|View full text |Cite
|
Sign up to set email alerts
|

Two-point observations of low-frequency waves at 67P/Churyumov-Gerasimenko during the descent of PHILAE: comparison of RPCMAG and ROMAP

Abstract: Abstract. The European Space Agency's spacecraft ROSETTA has reached its final destination, comet 67P/Churyumov-Gerasimenko. Whilst orbiting in the close vicinity of the nucleus the ROSETTA magnetometers detected a new type of low-frequency wave possibly generated by a cross-field current instability due to freshly ionized cometary water group particles. During separation, descent and landing of the lander PHILAE on comet 67P/Churyumov-Gerasimenko, we used the unique opportunity to perform combined measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 25 publications
(32 reference statements)
4
36
0
Order By: Relevance
“…We show two more examples of cometary waves and wave power spectra taken from the recent European Space Agency/NASA Rosetta spacecraft encounter with comet Churyumov‐Gerasimenko (comet “C.‐G.”). Figure (top) shows the large‐amplitude (~20 nT peak‐to‐peak in an ~40 nT magnetic field) “singing comet” waves (Richter et al, , ) which are not generated by ion pickup but presumably by a cross‐current (modified ion Weibel) instability (Glassmeier, ). Although the waves appear to be a discrete mode, there is also a high‐frequency wave portion above the pump frequency.…”
Section: Resultsmentioning
confidence: 99%
“…We show two more examples of cometary waves and wave power spectra taken from the recent European Space Agency/NASA Rosetta spacecraft encounter with comet Churyumov‐Gerasimenko (comet “C.‐G.”). Figure (top) shows the large‐amplitude (~20 nT peak‐to‐peak in an ~40 nT magnetic field) “singing comet” waves (Richter et al, , ) which are not generated by ion pickup but presumably by a cross‐current (modified ion Weibel) instability (Glassmeier, ). Although the waves appear to be a discrete mode, there is also a high‐frequency wave portion above the pump frequency.…”
Section: Resultsmentioning
confidence: 99%
“…The low-frequency (∼40 mHz) "singing comet waves" at 67P were first detected in August 2014 when Rosetta arrived at 67P (Richter et al 2015). More recently, Richter et al (2016) reported detection of singing comet waves from August 2014 until March 2015, when the heliocentric distance of 67P from the Sun varied from 3.6 to 2.0 AU. The waves are shown to be quasi-harmonic, large-amplitude (δB/B ∼ 1), low-frequency, and compressional in nature.…”
Section: Disappearance Of the Singing Comet Wavesmentioning
confidence: 99%
“…Prominent features are the increase in Bo and the rotation in the field direction. Detailed analyses of the magnetic field indicate the disappearance of low-frequency waves (tens of mHz), usually observed in the close plasma environment of the comet (Richter et al 2015(Richter et al , 2016Koenders et al 2016;Meier et al 2016), at the time of the outburst (see Sects. 2.3 and 2.4).…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that our model assuming an electric field wave works out quantitatively and there are mechanisms that could drive this wave, we conclude that waves are indeed shaping the IPS ion distribution in Pluto's wake. Comet 67P/Churyumov-Gerasimenko has been referred to as "the singing comet" (Glassmeier, 2017;Meier et al, 2016;Richter et al, 2016) thanks to its ULF waves for which we now also find evidence at "singing Pluto. "…”
Section: Discussionmentioning
confidence: 63%